응급실 얼굴 열상 환자에서 Modified Hollander 점수에 의한 조직 접착제 사용과 봉합사를 이용한 봉합 후 결과 비교 - 홍석호; 양영모; 이장영; 이원석; 박경남; 양희범 (Daehan oe'sang haghoeji, 2011)
Purpose: The object of this study is to compare the patient satisfaction in the view of scarring, cost, and hospital stay between the conventional suture method and a method using Histoacryl^®(2-N-butylcyanoacrylate)adhesive for treating facial lacerations in the emergency department. Methods: This study is a randomized prospective trial, which was conducted from December 2009 to January 2010. The participants include 109 patients who visited the emergency room in Deajon Eulji Medical Center. The ages ranged from 1 to 59 (mean age of 18.7), and all had facial lacerations of less than 3 cm. In order to treat the facial lacerations, an emergency medicine doctor used tissue adhesive (2-N-butylcyanoacrylate,Histoacryl^®) for 41 patients in the experimental group, and a plastic surgeon performed conventional suturing for 68 patients in the control group. The ER-stay and the primary treatment fee were compared in the two groups, and the scarring was evaluated 10 to 11 months from suturing by using the Modified Hollander Method and the 10-cm scaled VAS (visual analogue scale: score 0=no scar, score 10=very severe scar)Results: The ER stay was 76 minutes for the experimental group and 107 minutes for the control group,showing that statistically significantly less time of 31 minutes was taken in the experimental group. The cost of the experimental group was 40000 won (50.1%) more expensive than the control group, with an average cost of 121900 won for the experimental group and 81200 won for the control group. As for scar evaluation, 10.56months after suturing, the experimental group showed a better result with a score of 2.6 compared to a score of 3.4 in the control group; however, this difference was not statistically significant (p<0.05). As to a detailed evaluation of scar characteristics, the experimental group had a statistically significantly better result in scar elevation, with a score of 0.6 compared to a score of 1.65 for the control group. Conclusion: If appropriate patients are selected, the method using tissue adhesive directly applied by an EM doctor not only decreases ER stay but also creates similar patients satisfaction, with statistically better result in scar elevation, compared to the conventional suture method; thus, ultimately general patient satisfaction is increased. (J Korean Soc Traumatol 2011;24:143-150) KCI Citation Count: 0